Narrative und Diskurse in der Umweltpolitik. Möglichkeiten und Grenzen ihrer strategischen Nutzung. Zwischenbericht. - Espinosa, Cristina; Pregernig, Michael; Fischer, Corinna (My University, 2017)
Weitgehend auf eine Literaturanalyse von Studien zur Rolle von Diskursen und Narrativen in der Umweltpolitik gestützt, verfolgt dieser Bericht drei miteinander verknüpfte Ziele: Erstens werden zentrale Konzepte, wie sie in sprachsensitiven und diskursiven Theorieansätzen wie auch in empirischen Studien zu Umweltdiskursen verwendet werden, einer begrifflichen Klärung zugeführt, wobei besonderes Augenmerk auf die beiden Schlüsselkonzepte "Diskurs" und "Narrativ" gelegt wird. Zweitens werden wichtige Funktionen, die Narrative im politischen Prozess erfüllen können, dargestellt und sechs Hypothesen zu den Erfolgsbedingungen umweltpolitischer Narrative präsentiert und mit Beispielen bebildert. Drittens wird anhand von zwei Fallbeispielen, den Konzepten der "ökologischen Modernisierung" und des "Guten Lebens" und den darin eingeschriebenen Narrativen, aufgezeigt, wie Narrative als Kommunikationsinstrumente der Umweltpolitik eingesetzt wurden und welche praktischen Schlussfolgerungen sich daraus ziehen lassen. Aufbauend auf die vorhergehenden Analysen wird abschließend eine sogenannte "umweltpolitische Diskurslandkarte" als praktisches Instrument zur Einschätzung der Anschlussfähigkeit von Diskursen und Narrativen vorgestellt.

Environmental problems are not simply objective phenomena that can be rationally approached and resolved in a single, straightforward and effective way. Issues such as climate change, biodiversity loss, deforestation, desertification and many more, are imbued with power and subject to conflicting perspectives and interpretations which are highly context specific. These perspectives and interpretation integrally shape the way environmental problems are socially understood and dealt with by different means of organizing social co-existence such as politics. Accordingly, in the last three decades, language-sensitive and discursive approaches have become common for the study of environmental issues in the intersecting fields of sociology, political ecology and policy studies. Principally drawing from a literature review on the role of discourse and narratives in environmental politics, this report fulfils three interrelated aims: first, it clarifies key terms used in language-sensitive and discursive approaches for the study of environmental issues such as 'discourse' and 'narrative'. Second, it systematizes the key functions of narratives in politics and presents six hypotheses about the factors contributing to the success of narratives. Third, it provides illustrative examples and detailed accounts of the contents of successful narratives such as those interwoven in the two discourses of 'ecological mod-ernization' and the 'good life'. Finally, the report sketches out a 'discourse map' intended as an analytical tool to explore how new narratives link up with patterns available through different dominant discourses and neologisms shaping environmental politics. Overall, this report provides practical impulses for reflecting and developing strategies for a meaningful and successful communication of environmental problems in politics.
Keywords: Umweltschutz; Theorie; Umweltpolitik; Kommunikation; Literaturanalyse; Hypothese